Managing Inventory in Response to Varying Demand at Retail Store X to Reduce Stockouts - Devina Kristalia Irawan; Fransiska Hernina Puspitasari; Ika Murti Kristiyani (G-Tech: Jurnal Teknologi Terapan, 2025)
Both inventory shortages and excess inventory are among the issues encountered in inventory management. Lost sales are one of the impacts caused by inventory shortages. Retail Store X often experiences lost sales due to inventory shortages, such as cigarettes. Fluctuating demand and supplier terms make it difficult for this store to determine the order quantity sent to the supplier. Therefore, this research aims not only to minimize the number of stockouts but also complying with the supplier's requirement which is often disregarded in other research. The number of cigarettes that must be ordered must meet the minimum purchase under the agreed cooperation contract and the budget of Retail Store X that has been determined. This problem is solved using the periodic review system method, which relies on three parameters for the decision-making. This method calculates the order quantity for 10 cigarette products and then simulates over the next month to determine the number of stockouts that occur. Based on the results, one stockout incident was found for Tawang cigarettes amounting to two packs. Besides, the supplier requirement condition from the second supplier is also met and the purchase budget is fulfilled, which is below Rp450,000.00.